Continuous glucose monitoring in a patient with insulinoma presenting with unawareness of postprandial hypoglycemia - Rikako Nakajima; Hiroto Idesawa; Daisuke Sato; Jun Ito; Kei Ito; Masanao Fujii; Takamichi Suzuki; Tomoaki Furuta; Hitomi Kawai; Norio Takayashiki; Masanao Kurata; Hiroaki Yagyu (Endocrinology, Diabetes & Metabolism Case Reports, 2023)
Unawareness of postprandial hypoglycemia for 5 years was identified in a 66-year-old man at a local clinic. The patient was referred to our hospital because of this first awareness of hypoglycemia (i.e. lightheadedness and impaired consciousness) developing after lunch. In a 75 g oral glucose tolerance test, the plasma glucose concentration was decreased to 32 mg/dL (1.8 mmol/L) at 150 min with relatively high concentrations of insulin (8.1 μU/mL), proinsulin (70.3 pmol/L), and C-peptide (4.63 ng/mL). In a prolonged fasting test, the plasma glucose concentration was decreased to 43 mg/dL (2.4 mmol/L) at 66 h with an insulin concentration of 1.4 μU/mL and a C-peptide concentration of 0.49 ng/mL. Computed tomography showed an 18 mm hyperenhancing tumor in the uncinate process of the pancreas. A selective arterial calcium stimulation test showed an elevated serum insulin concentration in the superior mesenteric artery. The patient was then diagnosed with insulinoma and received pancreaticoduodenectomy. Continuous glucose monitoring (CGM) using the Dexcom G6 system showed unawareness of hypoglycemia mainly during the daytime before surgery. When the sensor glucose value was reduced to 55 mg/dL (3.1 mmol/L), the Dexcom G6 system emitted an urgent low glucose alarm to the patient four times for 10 days. Two months after surgery, an overall increase in daily blood glucose concentrations and resolution of hypoglycemia were shown by CGM. We report a case of insulinoma with unawareness of postprandial hypoglycemia in the patient. The Dexcom G6 system was helpful for assessing preoperative hypoglycemia and for evaluating outcomes of treatment by surgery.